Toward a global civil society - Walzer, Michael (New York : Berghahn Books, 1995)
The demise of Communism has not only affected Eastern Europe but also the countries of the West where a far-reaching examination of political and economic systems has begun. This collection of essays by internationally renowned scholars of political theory from Europe and the United States explores both the concept and the reality of civil society and its institutions.
Frontmatter -- Contents -- Foreword -- Introduction -- I The Concept of Civil Society -- 1. The Concept of Civil Society -- 2. Private and Public Roles in Civil Society -- 3. Interpreting the Notion of Civil Society -- 4. Reconceptualizing Civil Society for Now: Some Somewhat Gramscian Turnings -- 5. Civil Society, Hard Cases and the End of the Cold War -- II The Communitarian Approach -- 6. In Common Together: Unity, Diversity, and Civic Virtue -- 7. Too Many Rights, Too Few Responsibilities -- 8. Progressive Politics and Communitarian Culture -- 9. Neo-Hegelian Reflections on the Communitarian Debate -- 10. From Socialism to Communitarianism -- 11. On Labels and Reasons: The Communitarian Approach-Some European Comments -- III Economic Policy and Social Justice -- 12. Economic Policy and the Role of the State -- The Invisible, the Visible and the Third Hand -- 13. Industrial Policy -- Will Clinton Find the High Wage Path? -- 14. Redefining the Role of the State to Facilitate Reform in East and West -- 15. Between Social Darwinism and the Overprotective State -- Some Reflections on a Modern Concept of Social Welfare Policy -- 16. Civil Society and Social Justice -- 17. American Social Reform and a New Kind of Modernity -- IV The Internationalization of Politics and Economics and the Challenge of Nationalism, Immigration, and Minority Conflict -- 18. East European Reform and West European Integration -- 19. Rooted Cosmopolitanism -- 20. Ethnicity, Migration, and the Validity of the Nation-State -- 21. Neither Politics Nor Economics -- 22. The Left in the Process of Democratization in Central and Eastern European Countries -- V European Socialism and American Social Reform -- 23. After the Disappointment of the Epoch: American Social Tradition between Past and Future -- 24. Pluralism and the Left Identity -- 25. What's Left After Socialism -- 26. Some Reflections on the New World Order and Disorder -- Notes on Contributors -- Index
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Civil society -- United States; Civil society -- Europe; Social justice; Public welfare; Socialism; Post-communism.; Société civile -- États-Unis.; Société civile -- Europe; Justice sociale; Aide sociale; Postcommunisme; welfare services; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Sociology -- General; SOCIAL SCIENCE -- General; Civil society; Post-communism; Public welfare; Social justice; Socialism; Europe; United States